Peningkatan Kompetensi Guru dalam Menyusun Silabus dan RPP Melalui Supervisi Akademik Berkelanjutan - Abd. Main (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2023)
This article discusses efforts to increase teacher competence in compiling syllabus and lesson plans through continuous academic supervision. Teachers who are competent in preparing syllabus and lesson plans have an important role in improving the quality of learning in schools. However, teachers often face difficulties in planning lessons according to students' needs and the applicable curriculum. This study aims to analyze the effectiveness of academic supervision in increasing teacher competency in preparing syllabus and lesson plans. The research method used is a case study in several schools involving teachers who teach in various subjects. The results of the research show that continuous academic supervision has a positive impact on increasing teacher competence in preparing syllabus and lesson plans. Through academic supervision, teachers receive structured direction, guidance, and feedback from supervisors or authorities. This helps teachers to understand better the principles of developing effective syllabus and lesson plans.